PERANCANGAN SISTEM INFORMASI MANAJEMEN PROYEK : SISTEM PENGGAJIAN KARYAWAN - Sekti, Binastya Anggara (JIK: Jurnal Ilmu Komputer, 2019)
Humans who lived in the era of technology as it’s today definitely familiar with the implementation of technology in daily their life. Almost all human activities using technology, was no exception in the economy. The system is not only helpful but also simplify, shorten, and accurate, such as the Payroll System at PT Polymindo Permata. Every month an economic activity that has employees must have activity employee payroll as an appreciation of their work, as well as the PT Polymindo Permata. During this time the company is still recording and doing payroll calculations just using Microsoft Excel. It all doesn’t matter when the employees is just a few, but as the company grows, the number of employees was more and more. This poses a problem in the calculation and recording payroll. To overcome these problems, we need an appropriate system. The author would like to make a payroll system as a computer-based optimization of computing resources owned and can help finance the activities of employee payroll. By using the proposed system is expected to be more accurate calculation of payroll, time efficient, help to calculation cost of product and also more orderly financial reporting. Keyword : Payroll System, Project Management, Cost of Product